The Dhammapada and Ethical Teachings: Understanding the Importance and Significance in Modern Context - Nguyen Duy Chuong, (Dhammacakka Journal of Buddhism and Applied Buddhism, 2025)
The Dhammapada’s ancient verses, available in numerous languages and manuscripts since antiquity, continue to inspire individuals seeking a balanced and meaningful life. By presenting Buddhism as both a confirmation and a corrective to earlier Vedic teachings, it establishes a distinctive moral vision emphasizing freedom from craving, personal effort in spiritual progress, and the cultivation of wisdom and compassion. The Dhammapada is one of the most revered and widely studied texts in early Buddhist literature and ancient Indian spiritual writings. As part of the Theravāda Pāli Canon’s Khuddaka Nikāya, the Dhammapada has been recognized since ancient times as a core source conveying the essence of the Buddha’s moral philosophy in accessible language. The text’s emphasis on inner transformation rather than coercion highlights a universal moral framework grounded in compassion, mindfulness, and non-violence, which resonates profoundly in contemporary pluralistic societies. In today’s globalized world, where religious and cultural diversity is both a challenge and an opportunity, the Dhammapada offers ethical guidance that transcends sectarian boundaries. It teaches that liberation (Nibbāna), the ultimate goal of Buddhism, is attainable through the cultivation of the Noble Eightfold Path, comprising morality (Sīla), concentration (Samādhi), and wisdom (Paññā) along with the conditioned arising (paṭicca-samuppāda), and the impermanence of self (anattā) which provides a philosophical foundation for understanding human experience and moral responsibility without reliance on metaphysical dogma or rigid doctrines. Moreover, the text’s stress on moral discipline and mental cultivation remains highly relevant for addressing ethical dilemmas and fostering peace in modern life. This paper underscores how the Dhammapada remains a vital resource for understanding ethical conduct, mental wellbeing, and spiritual liberation in the contemporary world, making it a timeless guide for individuals and societies striving for harmony and enlightenment. The article further examines its ethical teachings, emphasizing their importance and relevance in the modern context. Central to the text is the Buddha’s practical vision of human behavior governed by moral causality (kamma-niyama), which underscores the principle that wholesome actions lead to beneficial outcomes, while unwholesome actions bring suffering. The teachings are not merely theoretical but are intended for lived experience, encouraging ethical conduct, mental purification, and insightful understanding to transcend ignorance and attachment.